Adult Renal Size is Not a Suitable Marker for Nephron Numbers: An Individual Patient Data Meta-Analysis - Ruud RG Bueters; Nicole CAJ van de Kar; Michiel F Schreuder (Karger Publishers, 2013)
Background: Renal size is often used as a marker for nephron numbers as estimation of glomerular numbers is not yet possible in vivo. However, the validity of an association between the two is questionable. As a proper marker for nephron number in an individual is needed in clinical practice, this study was designed to assess the association between renal size and nephron numbers. Methods: An individual patient data meta-analysis was performed on data retrieved with a PubMed and Embase search. Only studies were included that described individual human data on kidney size and nephron numbers determined by stereology, the gold standard methodology to estimate nephron numbers. As renal size increases until the end of puberty, and nephron numbers decline after the age of 60 years, only data from individuals aged 18-60 years without renal disease were included. Results: Six papers were identified that provided data on renal weight and nephron numbers from 114 individuals. Backward linear regression identified kidney weight and race as the only 2 significant factors explaining nephron numbers (R square 0.085, p=0.007). Controlling for race, there was a significant correlation between nephron number and kidney weight (r=0.231, r square=0.053, p=0.01). Conclusion: These data indicate that only ∼5% of the variation in nephron numbers is explained by differences in renal size. Renal size in adulthood should not be used as a marker for nephron numbers in an individual.